PENDAPATAN USAHATANI KOPI ORGANIK DIKAWASAN HUTAN - Suminartika, Eti; Utami, Hesti Nurul; Sadeli, Agriani Hermita (Agros Journal of Agriculture Science, 2024)
The number of coffee trees planted in forest areas is less than the number of coffee trees planted in farmers' gardens, coffee production grown in the forest is shared with Perhutani as the landowner, the selling price of organic coffee is higher than the selling price of anorganic coffee, organic coffee production costs tend to be lower because it only uses organic fertilizer which is much cheaper. The conditions of production yields, costs and receipts of organic coffee affect the income of coffee farmers in the forest.  The purpose of this study was to analyze the income of organic coffee farming in the forest farmer group (Kelompok Tani Hutan/KTH) Girisenang, Girimekar village, Cilengkrang sub-district, Bandung district. The research method used is a case study, the data used consists of primary and secondary data, primary data obtained from sample farmers by census.  The analysis used is descriptive analysis and mathematical analysis (farming analysis).    The results showed: The income of coffee plants per tree is IDR 5,431, the number of plants per hectare averages 1,272 trees, the income per hectare is IDR 6,892,968.  The R/C ratio value of organic coffee plants is 2.16, in other words, organic coffee plants in the perhutani forest area of Girimekar village, Cilengkrang sub-district, Bandung district are profitable.